Leaching of Zinc Sulfide by Thiobacillus ferrooxidans: Experiments with a Controlled Redox Potential Indicate No Direct Bacterial Mechanism - Fowler, T. A. (American Society for Microbiology, 1998)
The role of Thiobacillus ferrooxidans in bacterial leaching of mineral sulfides is controversial. Much of the controversy is due to the fact that the solution conditions, especially the concentrations of ferric and ferrous ions, change during experiments. The role of the bacteria would be more easily discernible if the concentrations of ferric and ferrous ions were maintained at set values throughout the experimental period. In this paper we report results obtained by using the constant redox potential apparatus described previously (P. I. Harvey and F. K. Crundwell, Appl. Environ. Microbiol. 63:2586–2592, 1997). This apparatus is designed to control the redox potential in the leaching compartment of an electrolytic cell by reduction or oxidation of dissolved iron. By controlling the redox potential the apparatus maintains the concentrations of ferrous and ferric ions at their initial values. Experiments were conducted in the presence of T. ferrooxidans and under sterile conditions. Analysis of the conversion of zinc sulfide in the absence of the bacteria and analysis of the conversion of zinc sulfate in the presence of the bacteria produced the same results. This indicates that the only role of the bacteria under the conditions used is regeneration of ferric ions in solution. In this work we found no evidence that there is a direct mechanism for bacterial leaching.